VALUE-FORMING CONCEPT OF EDUCATION OF PERSONALITY OF A SCHOOL STUDENT IN INDEPENDENT UKRAINE - Lemko, Halyna; Didukh, Iryna; Voroshchuk, Oksana (Mountain School of Ukrainian Carpaty, 2022)
The current period of social development is characterized by important processes that take place in the student environment. Under the influence of various social and political factors, new forms of thinking appear, specific values and value orientations are formed. The formation of value orientations among schoolchildren becomes particularly acute in modern society, which today is characterized by social instability, a crisis of spirituality, morality, and neglect of legal norms. Such a situation brings to the fore the problems of forming a new person, their consciousness and self-awareness, life values, spiritual forces, opportunities and abilities. In pedagogical science, the concept is interpreted as a system of views, which is significantly different from its theory or methodology due to the fact that the concept cannot be a finally verified constructor. It needs constant refinement, its theses can be debatable and require verification by facts, require the formulation of trends and regularities. The article analyzes the leading regulatory and legal documents containing relevant provisions on the foundations of the value-forming concept of personality education: State national program "Education" ("Ukraine of the 21st century"), The Law of Ukraine "On Education", the National Strategy for the Development of Education of Ukraine for the period until 2021, Concept of national education of student youth, Program of Ukrainian patriotic education of children and student youth, The concept of the New Ukrainian School, the regional targeted social program of national-patriotic education of children and youth for 2021-2025, approved by the Ivano-Frankivsk Regional Council. We also highlighted the relevance of building and implementing the concept of raising children and youth, highlighted the purpose of the concept of raising children and youth, and characterized the main principles of building the concept. Keywords: concept, values, education, schoolchildren, value-forming concept.